Lophopetalum tanahgambut, a new endemic giant tree species from peat swamp forest of Sumatera, Indonesia, with the first pseudoverticillate leaf arrangement in genus Lophopetalum (Celastraceae) - Randi, Agusti; Wijedasa, Lahiru S.; Utteridge, Timothy M.a. (Phytotaxa, 2022)
A new large tree species from peat swamp forest of Sumatera, Indonesia is described here with new notes on vegetative characters for the genus. Colour plates, as well as distribution, habitat, phenology, uses and observation notes are provided.